The vegetation as a botanical collection in the Parque do Flamengo, Rio de Janeiro - Farah, Ivete Mello Calil (Paisagem e Ambiente, 2021)
This paper focuses on the botanic aspects related to landscape architecture projetcts, highlighting the vegetation as a relevant element for designing urban landscapes. The exploratory essay is developed from the study of one of the most important leisure areas in Rio de Janeiro – the Parque do Flamengo. It was designed by Roberto Burle Marx, who stood out for his innovative use of vegetation, guided by the studies of botany and the advice of professionals in the area. Four topics support the analysis: the plant diversity caracteristic of the project; the unprecedented use of vegetation in urban areas; the presence of species at risk of extinction; and the use of unique plants in the landscape. Concerning the last point, the talipot-palm (Corypha umbraculifera) and its peculiar characteristics are highlighted. The paper points out the value of vegetation in landscape projects in urban areas as a botanic collection and emphasizes the need to implement scientific studies for greater knowledge about vegetation behavior in these areas, extending the subsidies for the use of this project tool.